Baby Dumping in Malaysia and Indonesia: Between National Regulation and Islamic Criminal Law (Mazahib, 2021)
This study aims to analyze the problem of baby dumping that happened in Malaysia and Indonesia according to regulation and Islamic Law (Fiqh al-Jinayah). As known, both countries are majority Muslims population which have similarities in terms of culture and customs. However, baby dumping cases are still happening in these countries, increasing every year. So it needs to be studied more deeply, considering that both countries have implemented laws related to the prohibition of baby dumping. This research is a normative method by descriptive qualitative type. This study concludes that baby dumping cases are not a light problem but a big problem that must resolve with the support of all parties. Some factors that influence a person in baby dumping cases are pregnancies outside of marriage, lack of education with knowledge of sex, embarrassment with the surrounding community. From the laws regulated in Malaysia and Indonesia, the perpetrators of this baby disposal can be subject to the most severe punishment as regulation implemented in both countries. However, the punishment for the perpetrators is still limited to imprisonment. Even if the perpetrators are children, child protection rules are applied. This punishment in Islam is categorized as ta'zir punishment. Keywords: Baby Dumping, Children, Islamic Law, Islamic Criminal Law